Genome sequence of Ensifer medicae Di28; an effective N(2)-fixing microsymbiont of Medicago murex and M. polymorpha - Garau, Giovanni (Stand Genomic Sci, 2014)
Ensifer medicae Di28 is an aerobic, motile, Gram-negative, non-spore-forming rod that can exist as a soil saprophyte or as a legume microsymbiont of Medicago spp. Di28 was isolated in 1998 from a nodule recovered from the roots of M. polymorpha growing in the south east of Sardinia (Italy). Di28 is an effective microsymbiont of the annual forage legumes M. polymorpha and M. murex and is capable of establishing a partially effective symbiotic association with the perennial M. sativa. Here we describe the features of E. medicae Di28, together with genome sequence information and its annotation. The 6,553,624 bp standard draft genome is arranged into 104 scaffolds of 104 contigs containing 6,394 protein-coding genes and 75 RNA-only encoding genes. This rhizobial genome is one of 100 sequenced as part of the DOE Joint Genome Institute 2010 Genomic Encyclopedia for Bacteria and Archaea-Root Nodule Bacteria (GEBA-RNB) project.